2012
DOI: 10.1074/jbc.m112.384552
|View full text |Cite
|
Sign up to set email alerts
|

Degradomics Reveals That Cleavage Specificity Profiles of Caspase-2 and Effector Caspases Are Alike

Abstract: Background:To study the potential role of caspase-2, we determined its cleavage site specificity and compared it with that of caspase-3 and -7. Results: N-terminal COFRADIC analysis of native proteomes revealed that caspase-2, -3, and -7 have overlapping specificities. Conclusion: Caspase-2, -3, and -7 share nearly indistinguishable cleavage site specificity. Significance: This finding suggests that caspase-2 has a proapoptotic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 76 publications
2
45
1
Order By: Relevance
“…In general, less than 3% of aspartic acid cleavage sites are detected in the absence of exogenous caspase, suggesting little caspase activation. Several small-scale studies have previously identified a total of 37 and 68 substrates for caspase-2 and caspase-6, respectively (11,22,23). More than half of the previously reported caspase-2 substrates were found in our dataset (19 of the 37), and we identified 13 of 61 caspase-6 substrates reported in the CutDB database (cutdb.burnham.org/).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In general, less than 3% of aspartic acid cleavage sites are detected in the absence of exogenous caspase, suggesting little caspase activation. Several small-scale studies have previously identified a total of 37 and 68 substrates for caspase-2 and caspase-6, respectively (11,22,23). More than half of the previously reported caspase-2 substrates were found in our dataset (19 of the 37), and we identified 13 of 61 caspase-6 substrates reported in the CutDB database (cutdb.burnham.org/).…”
Section: Resultsmentioning
confidence: 66%
“…[6][7][8]. By adding individual caspases to extracts, it has been possible to begin to identify caspasespecific substrates, ranging from just a few, in the case of caspase-4, caspase-5, and caspase-9 (9), to several hundred for caspase-1, caspase-3, caspase-7, and caspase-8 (10,11). Some of these substrates overlap, but others are unique to specific caspases.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition to providing unbiased information about which proteins are cleaved, in some cases, these experiments locate the precise sites and quantify the rates of cleavage.…”
Section: -5mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition to providing unbiased information about which proteins are cleaved, in some cases, these experiments locate the precise sites and quantify the rates of cleavage. [13][14][15][16][17] Using the subtiligasebased N-terminomics approach, we identified more than 1700 aspartate cleavage events distributed among about 1200 different protein substrates upon induction of apoptosis across seven human cell lines (http://wellslab.ucsf.edu/degrabase/).…”
mentioning
confidence: 99%
“…This progressive cleavage of rPaPARP may be explained by the presence of 25 arginine and 62 lysine residues representing potential cleavage sites of metacaspases. It is conceivable that there is a preference of metacaspases recognizing specific amino acids upstream of the P1 position of their substrate as it is characteristic for mammalian caspases (72). The amino acid sequences DEVD, YVAD, or VAD are known to be common cleavage sites for aspartate-specific caspases (8) but not for arginine-and lysine-specific metacaspases.…”
Section: Discussionmentioning
confidence: 99%